2019
DOI: 10.1111/ina.12548
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of contribution of metal pollution sources to attic and household dust in Pb‐polluted area

Abstract: Attic and household dusts from Pb‐polluted area were investigated using various analytical techniques for source apportionment and assessment of source contribution of metal‐bearing phases. Mineralogically, attic dust consists of gypsum, anhydrite, and metal‐bearing phases, while household dust comprises C‐bearing particles and only minor metal‐bearing phases. Sulfur isotope composition of sulfides and sulfates in attic dust shows that they result from past primary smelting of local sulfide ore, while those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In this site, located at 400 m from an industrial area (a non-ferrous metallurgical industry and a cement industry) in the south of Antwerp city, several elements of environmental concern were found in the present study at the highest concentrations, such as Cd, Cu, Ni, Pb and Sb, in addition to Ag, suggesting it as the most polluted site. Moreover, the presence of Zn in outdoor ANT sites could be due to organic matter degradation in urban parks near the study area; Zn is a micronutrient, therefore, it is commonly found in fertilizers and organic matter (Montalvo et al, 2016). However, Zn has also been identified in Flanders as related with traffic-emitted pollutants, such as elemental carbon, Cu, Cr and Fe (Vercauteren et al, 2011).…”
Section: Indoor/outdoor Elemental Pollutionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this site, located at 400 m from an industrial area (a non-ferrous metallurgical industry and a cement industry) in the south of Antwerp city, several elements of environmental concern were found in the present study at the highest concentrations, such as Cd, Cu, Ni, Pb and Sb, in addition to Ag, suggesting it as the most polluted site. Moreover, the presence of Zn in outdoor ANT sites could be due to organic matter degradation in urban parks near the study area; Zn is a micronutrient, therefore, it is commonly found in fertilizers and organic matter (Montalvo et al, 2016). However, Zn has also been identified in Flanders as related with traffic-emitted pollutants, such as elemental carbon, Cu, Cr and Fe (Vercauteren et al, 2011).…”
Section: Indoor/outdoor Elemental Pollutionmentioning
confidence: 99%
“…For those elements showing significant indoor-outdoor correlation and higher concentration in indoor moss (as observed in some sites for Al, Si and Co), progressive indoor accumulation due to a repeated entrance from outdoors (magnification) could be a conceivable explanation. In papers investigating indoor metal pollution by active samplers (e.g., Miler and Gosar, 2019;Pekey et al, 2010), element concentrations are expressed in mg per volume of air; therefore, a direct comparison between element concentrations is not feasible and the only parameter useful for comparison is the non-dimensional I/O ratio. In both the above mentioned articles, according to the I/O ratio, the authors found that metal-bearing particles were more abundant outdoors than indoors, consolidating our findings.…”
Section: Disentangling Metal Pollution Sources Between Indoor and Out...mentioning
confidence: 99%
See 2 more Smart Citations
“…Dust chemical/mineralogical composition is very variable and depends heavily on pathways and modes of introduction of pollutants into an indoor environment [16]. Minerals such as quartz and asbestos have toxic features that, despite numerous experimental studies in the field, their mechanisms of toxicity have not yet been fully clarified [17].…”
Section: Introductionmentioning
confidence: 99%